Variations of the Virome in Raw and Treated Water : A One-Year Follow-Up at Six Different Drinking Water Treatment Plants - Saguti, Fredy; Wang, Hao; Churqui, Marianela Patzi; Tunovic, Timur; Holmer, Linda; Pettersson, Ämma; Schleich, Caroline ; 0009-0007-4111-5305; Pott, Britt Marie; Bergstedt, Olof; Nyström, Kristina; Norder, Heléne (Environmental microbiology reports, 2025)
Little is known about virome changes in raw and drinking water over time, and differences between raw water sources and treatment technologies. This study used metagenomics to assess viruses prevalent in raw and drinking water samples over 1 year from six Swedish drinking water treatment plants (DWTPs) with varying treatment barriers and with different raw water sources. Sequences homologous to known viruses in the raw water samples were detected by amplification and next-generation sequencing and classified into 152 different virus species belonging to 76 virus families/orders. The majority were small bacteriophages. Other viral genomes were homologous to viruses infecting plants, invertebrates, vertebrates, mammals and giant viruses infecting amoeba or algae. Several virus species were simultaneously found in both raw and drinking water, indicating passage through the purification barriers, although reduced by 1–3 log10 after treatment. Most viruses detected in water samples after ultrafiltration were small viruses, and other barriers appeared more effective at removing smaller viruses. To avoid detecting viruses possibly replicating within DWTPs, viruses were separated according to the possibility that the host could be found in the water sources or not. These results underscore the importance of monitoring both raw and drinking water for small viruses, especially when viral contamination of the source water is at risk, to ensure drinking water quality.
Keywords: drinking water treatment plant; metagenomics; virome